Fenomenologi Pemilihan Kepala Desa Menggunakan Elektronik Voting - Pratama, Erwin Aditya (Diktum: Jurnal Ilmu Hukum, 2022)
The purpose of this paper is a legal study related to the phenoenology of holding village head elections using electronic voting in Boyolali Regency. The method used in this study is a socio-legal research approach sourced from collecting data obtained from primary data and secondary data, then analyzed by qualitative analysis methods. The results of the study provide answers to the legal study of the implementation of the village head election using electronic voting in Boyolali Regency are: MK Decision No. 147 / PUU-VII / 2009, Article 32 permendagri No. 112 Th. 2014 concerning village head elections, Article 20 boyolali district bylaws no. 11 th. 20016 concerning procedures for elections, appointment and dismissal of village heads, Boyolali Perbup No. 55 Th. 2012 concerning procedures for the implementation of village head elections. The use of e-voting in village head elections in Boyolali District will not work well if the stages do not go well. The socialization that is the basis of the socio-legal implications related to the use of new methods in this election has also been intensified. Based on the above, the key to the success and effectiveness of a Village Head election is the electoral process.